DSM-5 Insomnia and Short Sleep: Comorbidity Landscape and Racial Disparities - Kalmbach, David A.; Pillai, Vivek; Arnedt, J. Todd; Drake, Christopher L. (Sleep (New York, N.Y.), 2016)
Abstract Study Objectives: We estimated rates of cardiometabolic disease, pain conditions, and psychiatric illness associated with Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) insomnia disorder (current and in remission) and habitual short sleep (fewer than 6 h), and examined the roles of insomnia and short sleep in racial disparities in disease burden between black and non-Hispanic white Americans. Methods: This epidemiological survey study was cross-sectional. The community-based sample consisted of 3,911 subjects (46.0 y ± 13.3; 65.4% female; 25.0% black) across six sleep groups based on DSM-5 insomnia classification (never vs. remitted vs. current) and self-reported habitual sleep duration (normal vs. short). Vascular events, cardiometabolic disease, pain conditions, and psychiatric symptoms were self-reported. Results: Short sleeping insomniacs were at elevated risk for myocardial infarction, stroke, treated hypertension, diabetes, chronic pain, back pain, depression, and anxiety, independent of sex, age, and obesity. Morbidity profiles for insomniacs with normal sleep duration and former insomniacs, irrespective of sleep duration, were similar with elevations in treated hypertension, chronic pain, depression, and anxiety. Regarding racial disparities, cardiometabolic and psychiatric illness burden was greater for blacks, who were more likely to have short sleep and the short sleep insomnia phenotype. Evidence suggested that health disparities may be attributable in part to race-related differences in sleep. Conclusions: Insomnia disorder with short sleep is the most severe phenotype of insomnia and comorbid with many cardiometabolic and psychiatric illnesses, whereas morbidity profiles are highly similar between insomniacs with normal sleep duration and former insomniacs. Short sleep endemic to black Americans increases risk for the short sleep insomnia phenotype and likely contributes to racial disparities in cardiometabolic disease and psychiatric illness.